Organizational Commitment among the Personnel of the Select Private College in the Philippines - Pabelona, Rechie B.; Bulahan, Roy I. (International Journal of Scientific Research and Management (IJSRM), 2023)
The study aims to determine the organizational commitment among personnel of the select private college in the Philippines. The respondents of the study were the 143 full time personnel of the organization and they were group according to age, sex, length of service and work area (department). The results shows that both the young and old category show that the normative commitment received the highest mean while continuance commitment got the lowest mean.  When grouped according to sex, the result shows that the female category had a higher mean compared to the male category and both got the slightly positive verbal interpretation. When grouped according to length of service, the result shows that longer category had a higher mean compared to the shorter category and both got the slightly positive verbal interpretation. In the short category the normative commitment received the highest mean, while for the long category the affective commitment had the highest mean. In both category continuance commitment received the lowest mean. When grouped according to work, the result shows that SARFAID and NTP received the highest overall mean and ANTP received the lowest overall mean. Overall results got the verbal interpretation of slightly positive. In terms of affective commitment, it shows that ADMIN received the highest mean and the lowest mean is from ANTP department. For continuance commitment, it shows that GM received the highest mean with the verbal interpretation of slightly positive while the lowest is from the ADMIN with slightly negative interpretation. The normative commitment results reflect that SARFAID received the highest mean with the verbal interpretation of positive, while the lowest mean with the verbal interpretation of slightly positive is from ANTP department. When grouped according to work area it is significant. Based from the foregoing result, the researcher recommends that: The school should create a program to improve organizational commitment of its employees and minimize their turnover.